A formação de professores de Ciências na licenciatura em Educação do Campo: tecendo tramas na Alternância - Cardoso, Elisandra Carneiro de Freitas (2020)
The present work aims to understand how the UFG - Regional Goiás - Graduation in Education for Rural Schools promotes the formation of Science teachers that dialogue with the Alternation strategy in order to understand the positioning from the course in front of training teachers for Rural Schools. In order to achieve the general objective, we list as specific objectives: 1) to record the paths taken for the implementation of LEdoC at UFG; 2) to understand the principles of Rural Education and Alternation; 3) to report how the formation of Science teachers through Alternation occurs; 4) identify the strategies used in the course to achieve Alternation; and 5) to think about positioning of course in front of training teachers for Rural Schools. It is a qualitative research in which we adopt participative research as a form of investigation, as it is based on a personal commitment between the researcher and the object and is built from a humanizing perspective for reality. To collect of data, we adopted the analysis of the Pedagogical Project of the Course and the participation in planning meetings and activities developed during Time-Community (TC). We participated at eight collegiate meetings and five TC planning and evaluation meetings, totaling thirteen meetings recorded and transcribed. The activities developed at the TC included participation in the opening and closing, in the orientation meetings of the TC groups and activities in the communities, totaling a number of seventeen meetings. For the analysis we chose the following categories: Planning, Time, Alternation, Evaluation, Generating Theme, Interdisciplinarity, Dialogue, Contextualization, Collectivity, Culture and Praxis. The results showed that PPC lacks clarity in relation to the pedagogical proposal in Alternation, because although the document expresses the articulation between Time-University and Time-Community, it still seems that happens in a fragile way, which becomes an obstacle to the realization of an Integrative Alternation. Otherwise, planning, evaluation and co-work are elements of the pedagogical practice of teachers whose are fundamental trainers to articulate the integration between formative times. In this sense, it is necessary to break with practices and customs of non-involvement and not belonging to a formative process forged in social struggles, since the Rural Education movement requires a commitment to the community and to the integral and human formation of the peasantry, which it cannot be promoted without the attitude of listening to the other, of dialogue and collaboration. A transformative element in the Alternation of the course is the adoption of specific pedagogical instruments for LEdoC, allowing the dialogue of knowledge, the breaking of disciplinary barriers and the articulation between formative times, which is close to the Integrative Alternation. Despite UFG having built a trajectory with the peasantry issue, it does not have a locus for discussing an institutional policy that serves the subject of the field. Regional Goiás is still hostage to the lack of institutional support for the development of training processes that include the peasantry as subjects of law. In view of this, we understand that Alternation at LEdoC/UFG -Regional Goiás - has been built on the dialectic between breaking with practices embedded in education model that does not include the Rural area and its subjects and the structuring of paths that produce a human formation, critical and rooted in the reality of the countryside.